2010
DOI: 10.1111/j.1600-0714.2010.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer in Myanmar: a preliminary survey based on hospital-based cancer registries

Abstract: The occurrence of oral cancer is not clearly known in Myanmar, where betel quid chewing habits are widely spread. Since betel quid chewing has been considered to be one of the important causative factors for oral cancer, the circumstantial situation for oral cancer should be investigated in this country. We surveyed oral cancer cases as well as whole body cancers from two cancer registries from Yangon and Mandalay cities, both of which have representative referral hospitals in Myanmar, and we showed that oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
4
21
1
Order By: Relevance
“…In agreement with reports from Yemen [12,18,19], Saudi Arabia [23], Kuwait [27], Myanmar [25] and many other developed and developing countries [3], the tongue was the most affected oral subsite in men and women. Differences between regions have been reported however.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with reports from Yemen [12,18,19], Saudi Arabia [23], Kuwait [27], Myanmar [25] and many other developed and developing countries [3], the tongue was the most affected oral subsite in men and women. Differences between regions have been reported however.…”
Section: Discussionsupporting
confidence: 90%
“…Unexpectedly, the relative frequency of pharyngeal cancer was higher compared with other reports from Yemen [12][13][14]18] and other countries [7,[23][24][25][26][27][28][29]. Nasopharyngeal cancer, which accounted for more than 89% of the pharyngeal cancers in the present study, is relatively common among Iraqi [21] and western North African men [30] and among the Chinese [5].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The most common site of OSCC in both age groups in our study was the tongue, which is in agreement with the findings of many previous studies (14,15,23,29,30). This result is also in line with the analysis from multinational cancer registries in both developed and developing countries in all regions of the world except for south-central Asia, where the most common sites were found to be the gingiva and buccal mucosa (1).…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, some studies have reported that the tumor site is related to specific risk factors (5,6,15,18,(30)(31)(32). Tumors of the tongue and the floor of the mouth may be associated with excessive alcohol consumption and cigarette-smoking habits (1,6,29,32), whereas lesions on the buccal mucosa and gingiva may be related to tobacco/betel quid chewing habits (1,6,18,30). Taken together, these factors could explain the low percentages of tumors on the gingiva and buccal mucosa in the young group in our study.…”
Section: Discussionmentioning
confidence: 99%